Distinct roles for nucleic acid in in vitro assembly of purified Mason-Pfizer monkey virus CANC proteins - Ulbrich, Pavel; Haubova, Sarka; Nermut, Milan V; Hunter, Eric; Rumlova, Michaela; Ruml, Tomas (Journal of virology, 2006)
In contrast to other retroviruses, Mason-Pfizer monkey virus (M-PMV) assembles immature capsids in the cytoplasm. We have compared the ability of minimal assembly-competent domains from M-PMV and human immunodeficiency virus type 1 (HIV-1) to assemble in vitro into virus-like particles in the presence and absence of nucleic acids. A fusion protein comprised of the capsid and nucleocapsid domains of Gag (CANC) and its N-terminally modified mutant (DeltaProCANC) were used to mimic the assembly of the viral core and immature particles, respectively. In contrast to HIV-1, where CANC assembled efficiently into cylindrical structures, the same domains of M-PMV were assembly incompetent. The addition of RNA or oligonucleotides did not complement this defect. In contrast, the M-PMV DeltaProCANC molecule was able to assemble into spherical particles, while that of HIV-1 formed both spheres and cylinders. For M-PMV, the addition of purified RNA increased the efficiency with which DeltaProCANC formed spherical particles both in terms of the overall amount and the numbers of completed spheres. The amount of RNA incorporated was determined, and for both rRNA and MS2-RNA, quantities similar to that of genomic RNA were encapsidated. Oligonucleotides also stimulated assembly; however, they were incorporated into DeltaProCANC spherical particles in trace amounts that could not serve as a stoichiometric structural component for assembly. Thus, oligonucleotides may, through a transient interaction, induce conformational changes that facilitate assembly, while longer RNAs appear to facilitate the complete assembly of spherical particles.
Keywords: Protein Structure, Tertiary; bezbuněčný systém; Mason-Pfizer monkey virus; Virus Assembly; kapsida; HIV-1; mutace; sestavení viru; RNA, Viral; Oligonucleotides; Capsid; Gene Products, gag; Protein Conformation; Mutation; zvířata; Cell-Free System; Humans; genom virový; genové produkty gag; oligonukleotidy; RNA ribozomální; RNA, Ribosomal; Masonův-Pfizerův opičí virus; RNA virová; terciární struktura proteinů; Genome, Viral; lidé; konformace proteinů; Animals